SINERGI AKADEMISI-PETANI: OPTIMALISASI POTENSI EKONOMI DESA GUNTUNG BESAR MELALUI LITERASI KEUANGAN - Prabowo, Janitra; Prabowo, Kristianto Tricahya; Syahputra, M. Fadly; Hady, Anindya Ratna Kartika; Mahmudah, Mahmudah; Ramadhani, Agnes (STIE Pelita Nusantara, 2025)
This community service program demonstrates how financial literacy-based synergy between academics and farmers optimize economic potential in Guntung Besar Village, South Kalimantan. Despite rich argicultural resources (rice, palm oil, rubber), low financial literacy among farmers led to loan shark dependence and underutilization of formal financing. Through contextual workshops and field mentoring involving D4 Akuntansi Perpajakan Politeknik Negeri Tanah Laut, BUMDes and farmers, the initiative achieved reduction in loan shark dependence, increase in BUMDes utilization, and adoption of practical financial recording systems.The innovative “Agro-Accounting Model” – featuring crop-cycle periodozation and localized cost classification – overcame challenges like farmer group fragmentation through monthly village forums and cooperative formation. Loan shark resistance was transformed into distributor partnerships via profit-sharing schemes. Sustainability is institutionalized through Village Regulation, youth cadre training, and academic curricullum integration. Results validate experiental learning principle, showing field-based financial education triple concept adoption compared to classroom methods. This initiative proves agricultural financial literacy serve as foundational leverage for rural economic transformation when combined with tridharma synergy and cultural wisdom.